2013
DOI: 10.1093/cercor/bht125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex and Gonadal Steroids on Neonatal Brain Structure

Abstract: There are numerous reports of sexual dimorphism in brain structure in children and adults, but data on sex differences in infancy are extremely limited. Our primary goal was to identify sex differences in neonatal brain structure. Our secondary goal was to explore whether brain structure was related to androgen exposure or sensitivity. Two hundred and ninety-three neonates (149 males) received high-resolution structural magnetic resonance imaging scans. Sensitivity to androgen was measured using the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 103 publications
(105 reference statements)
10
35
3
Order By: Relevance
“…Nevertheless, specific frontal, temporal, and parietal cortex regions, known to be involved in hand gesture imitation (Perkins, Bittar, McGillivray, Cox, & Stokes, ), displayed different activation patterns in male‐biased neurodevelopmental disorders such as autism. Larger volume of the orbitofrontal cortex, involved in social cognition, has been shown in females during childhood and adulthood (Knickmeyer et al, ). Our time‐related evaluation of pointing may be consistent with a faster maturation of social skills in girls that was persistently observed in the long‐term GMDS assessment by personal–social subscale where females showed better outcomes in activities of daily living, level of independence, and social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, specific frontal, temporal, and parietal cortex regions, known to be involved in hand gesture imitation (Perkins, Bittar, McGillivray, Cox, & Stokes, ), displayed different activation patterns in male‐biased neurodevelopmental disorders such as autism. Larger volume of the orbitofrontal cortex, involved in social cognition, has been shown in females during childhood and adulthood (Knickmeyer et al, ). Our time‐related evaluation of pointing may be consistent with a faster maturation of social skills in girls that was persistently observed in the long‐term GMDS assessment by personal–social subscale where females showed better outcomes in activities of daily living, level of independence, and social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on infancy and early childhood are more limited, but indicate that many of these sex differences are present at birth. Male neonate brains are about 6% larger than female brains at birth, and even at this stage there are already several areas that evidence local sexual dimorphism 123 . For example, the medial temporal cortex and rolandic operculum are larger in males, whereas the dorsolateral prefrontal, motor, and visual cortices are larger in females 123 .…”
Section: Influences Of Genes and Environmentmentioning
confidence: 98%
“…Male neonate brains are about 6% larger than female brains at birth, and even at this stage there are already several areas that evidence local sexual dimorphism 123 . For example, the medial temporal cortex and rolandic operculum are larger in males, whereas the dorsolateral prefrontal, motor, and visual cortices are larger in females 123 . A more recent study with a larger sample size and more stringent statistical thresholds replicated the finding of increased medial temporal cortex in males and also indicated that female neonates have greater grey-matter volumes around the temporal-parietal junction, a crucial brain region for social cognition 124 .…”
Section: Influences Of Genes and Environmentmentioning
confidence: 98%
“…These findings of atypical regional brain growth in girls with ASD correspond with the fact that these girls show greater signs of many cognitive and behavioral impairments than boys. Given that striking sex differences exist in the typical neonatal, infant, and adolescent brain as well as in brain developmental trajectories (Gilmore, Lin et al 2007, Lenroot, Gogtay et al 2007, Lenroot and Giedd 2010, Giedd, Raznahan et al 2012, Knickmeyer, Wang et al 2014), future longitudinal studies during these developmental periods are needed to confirm whether similar sex differences in ASD neuroanatomy still hold.…”
Section: Sex Differences In the Neuroanatomy And Structural Connectivmentioning
confidence: 99%